2019
DOI: 10.3390/rs11232744
|View full text |Cite
|
Sign up to set email alerts
|

A Review of Regional and Global Gridded Forest Biomass Datasets

Abstract: Forest biomass quantification is essential to the global carbon cycle and climate studies. Many studies have estimated forest biomass from a variety of data sources, and consequently generated some regional and global maps. However, these forest biomass maps are not well known and evaluated. In this paper, we reviewed an extensive list of currently available forest biomass maps. For each map, we briefly introduced the data sources, the algorithms used, and the associated uncertainties. Large-scale biomass data… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
52
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 57 publications
(55 citation statements)
references
References 126 publications
(201 reference statements)
3
52
0
Order By: Relevance
“…The validation result was somehow overoptimistic because some of the reference data were compiled from satellite-derived biomass datasets with spatial resolutions of 500 m and 1 km. Previous studies suggested that a global forest biomass map provided by Yang et al [23] was close to that from Hu et al [8], when validated with field reference AGB or evaluated in terms of spatial distribution [11,71]. Therefore, compared with previous studies, this study provided a feasible way to produce accurate forest AGB maps on a global scale.…”
Section: Discussionsupporting
confidence: 51%
See 1 more Smart Citation
“…The validation result was somehow overoptimistic because some of the reference data were compiled from satellite-derived biomass datasets with spatial resolutions of 500 m and 1 km. Previous studies suggested that a global forest biomass map provided by Yang et al [23] was close to that from Hu et al [8], when validated with field reference AGB or evaluated in terms of spatial distribution [11,71]. Therefore, compared with previous studies, this study provided a feasible way to produce accurate forest AGB maps on a global scale.…”
Section: Discussionsupporting
confidence: 51%
“…Based on both types of data, many forest AGB maps were produced at local, regional, or global scales using various algorithms [2][3][4][5][6][7][8]. However, due to the uncertainties associated with the selection of allometric equations to calculate field biomass and the uncertainties in remote sensing datasets and the algorithms used for AGB prediction, substantial uncertainties remain in current AGB estimates [11][12][13]. To improve the accuracy of AGB estimation, some recent studies have proposed that efforts should be made to compile field biomass extensively, integrate multiple remote sensing datasets, explore novel approaches, and comprehensively address the uncertainty associated with biomass estimates [11,[14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…We used other regional and global forest AGB maps (see Table III) to do the comparison with our map. The global forest AGB map produced by Zhang and Liang [55] (subsequently called the Z map) was not yet published and was obtained through contact with the author. We calculated the difference maps from the pixel value of our forest AGB estimated map minus the corresponding pixel value of the other forest AGB maps.…”
Section: Accuracy Assessmentmentioning
confidence: 99%
“…1) North America: For North America, we used forest AGB maps derived by Thurner et al [58] (the T map), Hu et al [57] (the H map), and Zhang and Liang [55] (the Z map) for comparison with our forest AGB map.…”
Section: Comparison With Other Regional Forest Agbmentioning
confidence: 99%
“…If current global forest cover maps have issues estimating existing tree cover and restoration potential in dry biomes, then what are the possible solutions? First, there are alternative maps of global forest cover and biomass that use microwave (SAR; Synthetic Aperture Radar) data instead of MODIS and Landsat optical data (Martone et al., 2018; Shimada et al., 2014; Zhang, Liang, & Yang, 2019). Because they can penetrate cloud cover and potentially map wet season tree cover, SAR‐derived maps could be more accurate in drylands and are a promising approach.…”
Section: Ways Forward: Creating Corrected Estimatesmentioning
confidence: 99%